Fukushima's Non-Nuclear Power Plants: Their History, Damage by Disasters, and Prospects for the Future. Issue 5 (September 2013) - Ofuji, Kenta
The Great East Japan Earthquake that struck in March 2011 directly damaged Fukushima Prefecture. Due to the ensuing nuclear accident of Fukushima Daiichi plant, the Prefecture's power output decreased by 9GW. However, Fukushima Prefecture has more than just nuclear power. Prior to the earthquake, the prefecture was Japan's biggest power-supplying prefecture because of its abundant hydro and thermal power. After the nuclear power plant accident, aversion to nuclear power naturally intensified in Fukushima Prefecture. Despite this, in the future, the prefecture will continue to be a power-supplying prefecture primarily via thermal and hydro power. The author, living in Fukushima, argues that the revival and bolstering of thermal and hydro power will help to dispel concerns about Japan's power supply and may also facilitate local economic recovery.